Implementation Of the Village Company Program for Citizens (SADEWA) For Community Welfare - Nunun Nurhajati; Laily Purnawati; Angkasawati; Dwi Iriani Margayaningsih (Lafadz Jaya Publisher, 2024)
Kendalbulur Village is one of the villages in Tulungagung and has the only Village Compensation for Residents (SADEWA) program. This program is intended for underprivileged communities that have not yet entered the integrated social welfare data (DTKS). The Compensation Program from Villages for Residents (SADEWA) is provided to increase residents' income, improve the welfare of village communities, and accommodate various economic business activities in village communities. This research study focuses on analyzing the implementation of the SADEWA program based on Merilee S. Grindle's policy implementation theory in Kendalbulur Village, Boyolangu subdistrict, Tulungagung district. Descriptive qualitative research is the chosen method, which collects data using interviews and observations using purposive sampling. The SADEWA program provides health subsidies, non-academic education subsidies, agricultural subsidies, and Land and Building Tax (PBB) subsidies. The local community has felt the benefits of this program because it has improved their welfare. However, obstacles still need to be found, namely the need for more innovation in tourism development.